Zero Generation Holocaust Literature - Goldwyn, Adam J. author. (orcid)0000-0001-6175-8593 Link aut Link
VIII, 253 p. 1 illus.
Keywords: This book is about “zero generation” witness literature: texts written by those who died in the Holocaust and who knew, at the time of their writing, that they would not survive. As such, they offer a unique perspective that differs from the more widely read and taught literature written by first generation survivors like Elie Wiesel and Primo Levi. These texts were produced across the concentrationary universe and include: the ghetto diaries of Dawid Sierakowiak (Łódź) and Chaim Kaplan (Warsaw); transit camp work, such as the paintings of Felix Nussbaum (Saint-Cyprien) and the poetry of Yitchak Katznelson (Vittel); anonymous letters thrown from cattle cars; Sonderkommando writing and photography from Auschwitz; non-Jewish letter-writing from Gestapo prisons by Helmuth-James and Freya Von Moltke (Tegel); and the literary work of Hannah Szenes, from her diaries in Palestine to her last poetry and letter in a Budapest prison the day of her execution. Adam J. Goldwyn is Professor of English at North Dakota State University, USA. He is the author, most recently, of Homer, Humanism, Holocaust (Palgrave Macmillan, 2022), Rae Dalven: The Life of a Greek-Jewish Immigrant (2022), and Witness Literature in Byzantium (Palgrave Macmillan, 2021).